Cancellation of the more complicated ophthalmic inpatient surgeries in a tertiary general hospital: a 10-year retrospective study - Zhao, Xinyu; Zhao, Qing; Wu, Yanfang; Cheng, Shiyu; Wang, Chuting; Meng, Lihui; Gu, Xingwang; Chen, Youxin (Frontiers in Medicine, 2024)
Background: Although ophthalmic ambulatory surgeries are less costly and may enhance the more efficient utilization of hospital resources, inpatient surgeries were preferable alternatives for patients with complicated eye diseases or poor general health. However, the incidence, causes, and related factors of ophthalmic inpatient surgery cancellation remained largely unknown.The electronic medical records of ophthalmic inpatient surgeries between January 2012 and December 2022 was retrospectively reviewed. Cancellation-related factors were explored using multivariate logistic regression analysis and the reasons of cancellation were also evaluated.In total, 820 cancelled surgeries and 42,073 performed surgeries were included, with a cancellation rate of 1.9%. Any other ocular comorbidities were risk factors for cancellation (odds ratio (OR) 1.872, 95% confidence intervals (CI) 1.504-2.331; P < 0.001), while older age (OR 0.990, 95% CI 0.986-0.995; P < 0.001), local residence (OR 0.809, 95% CI 0.692-0.947; P = 0.008), any systemic comorbidities (OR 0.740, 95% CI 0.616-0.889; P = 0.001), and previous history of surgeries (OR 0.403, 95% CI 0.341-0.476; P < 0.001) were negatively associated with surgery cancellation. The top two categorical cancellation reasons were medical factors (508, 62.0%) and patient-related factors (285, 34.8%). "Patient/family refused surgery" (127, 15.5%), "acute conjunctivitis or uveitis relapse" (103, 12.6%), and "ocular condition improved and procedure no longer indicated" (71, 8.7%) were the three most common single cancellation reasons.Any other ocular comorbidities, younger age, no systemic comorbidities, non-local residence, and no past surgical history were related factors for ophthalmic inpatient surgery cancellation. The majority of cancellations were due to patient-related or medical factors. Great importance should be attached to the cancellation of the more complicated inpatient surgeries and further efforts are warranted to explore how to reduce cancellation.